INVESTIGATION OF ANTIOXIDANT POTENTIALS OF SOLVENT EXTRACTS FROM DIFFERENT ANATOMICAL PARTS OF ASPHODELINE ANATOLICA E. TUZLACİ: AN ENDEMIC PLANT TO TURKEY - Zengin, Gokhan; Aktumsek, Abdurrahman (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The genus Asphodeline (Liliaceae) is represented in Turkey by 20 taxa, which are traditionally used for medicinal purposes in Anatolia. Materials and Methods: In this study, we tested the phytochemical content and antioxidant effect of different solvent extracts obtained from different anatomical parts of Asphodeline anatolica. The different extracts of each plant parts were tested for antioxidant activity using different chemical assays. The total antioxidant components were also calculated. Results: Generally, acetone extracts produced the seed and root exhibited significantly higher antioxidant activity with high antioxidant components. Total phenolic content of extracts were significantly correlated with antioxidant potentials (except for, metal chelating activity). Conclusion: On the basis of the results obtained, A. anatolica extracts should be regarded as a valuable source of natural antioxidants for food and therapeutic applications.